Optimal Transmission Switching for Congestion Management and Cost Reduction Using Linearized AC Optimal Power Flow - Mohammad Habibi; Ali Zangeneh (International Transactions on Electrical Energy Systems)
Several approaches have been introduced to manage congestion in transmission lines while simultaneously reducing the generation cost of power systems. Two of these approaches, namely, generation rescheduling and transmission switching are used together in this article. Changing the system topology through optimal transmission switching (OTS) is an important and active research area in power systems for this purpose. Essentially, OTS is a mixed-integer nonlinear programming (MINLP) problem that is inherently nonlinear and nonconvex. Therefore, solving this nonlinear problem poses significant challenges for researchers. On one hand, there is no guarantee of reaching a global optimal solution, and on the other hand, issues such as the lack of convergence and increased solution time have made it difficult to solve the OTS problem. Linearizing the OTS problem provides a guaranteed method for reaching a comprehensive optimal solution. This study presents a new linear mathematical model for the OTS problem. The proposed model is solved using mixed-integer linear programming (MILP), which accurately determines the opening or closing status of transmission lines and the number of lines that should be opened to reduce the generation and congestion costs in the network. To this aim, a linear programming and piecewise approximation, along with Taylor’s series approximation method, is used to linearize the generation cost function, and AC optimal power flow equations. To reduce the solution time of the OTS problem without losing accuracy, a congestion cost index is used based on decreasing the total congestion cost of transmission lines, as well as the production cost of generators. The proposed model is implemented on IEEE 9-bus and IEEE 118-bus standard test systems. Also, in order to analyze the reliability of the system before and after switching, two methods of contingency analysis and calculation of the LOLP index have been used. The obtained results show that transmission switching can reduce the generation cost and the total power system congestion cost as well.